2021
DOI: 10.5603/demj.a2021.0014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency of the paediatric brain CTs with trauma and non-trauma related indications in the paediatric emergency department

Abstract: BACKGROUND:This study aimed to determine the appropriateness of the examinations by evaluating the pre-diagnosis of the patients who underwent brain Computed Tomography (CT) in the paediatric emergency departments and the existing pathologies in the brain CTs. In addition, a comparison of the efficiency of the brain CT examinations performed for trauma and non-traumatic reasons was made. MATERIAL AND METHODS:CT's were examined by dividing into 2 groups according to the indications as trauma (group 1) and non-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…post traumatic and nontraumatic. Dogan et al reported that 83% CT scans of the head performed in the EDs are injury-related and the rest (17%) come from non-traumatic reasons [7]. In the study, traumatic lesions observable on CT were found in 19.8% of the examined children, while 80.2% had non-traumatic lesions.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…post traumatic and nontraumatic. Dogan et al reported that 83% CT scans of the head performed in the EDs are injury-related and the rest (17%) come from non-traumatic reasons [7]. In the study, traumatic lesions observable on CT were found in 19.8% of the examined children, while 80.2% had non-traumatic lesions.…”
Section: Discussionmentioning
confidence: 64%
“…The preliminary diagnoses of patients who underwent a CT for other than traumatic causes, include with decreasing incidence: headaches, seizures, fever, confusion, hematoma, infarct, optic neuritis and arrest [7]. In the study headaches are also the most common indication for non-traumatic reason.…”
Section: Indications For Performing a Ct Scan (Prediagnosis)mentioning
confidence: 99%
See 2 more Smart Citations